Characteristics of A6061/(Glass Fibre + AL2O3 + SiC + B4C) Reinforced Hybrid Composite Prepared through STIR Casting - Subramani Nanjan; Ganesh Murali Janakiram (Advances in Materials Science and Engineering)
In this article, A6061 and its reinforcement particles like aluminium oxide/glass fibres/SiCp/B4C (4% and 5%) with mixed composite and aluminium oxide/SiCp/B4C mixed without glass fibre composite are produced with different proportions using the stir casting method. Here, some experimental study is carried out on the composite layer through scanning electron microscopy and XRD test to show the influence of the reinforcement on A6061, and the percentage of gold-silver-copper (AuAgCu), aluminium-zinc (ZA), and palladium deuteride is increased in this composition and justified through the graphical representation of the XRD image. Mechanical properties of the stir casting composites were evaluated through microhardness, wear test under 200 rpm and 300 rpm and 20 N and 50 N, and tensile tests. The results were compared with the properties of the base metal, with glass fibre reinforcement specimen and without adding glass fibre specimen; this will help us to check the strength and weakness of the glass fibres in A6061.